Aircraft Fuel Heat Sink Utilization - Gray, Charles N.; Shayeson, Maurice W. (1973)
This report identifies fuel temperature levels and contributors to fuel temperature rise or decrease at each step of fuel handling or usage from ground bulk storage to engine combustor. The program consisted of a literature search and review of available information on fuel temperatures in bulk storage and on-loaded aircraft tanks, flight profile effects on fuel tank fuel temperature, and fuel temperature changes resulting from aircraft and engine heat loads in flight. The study program was supplemented by MINEX thermal stability tests on JP fuels by the USAF. The results indicate a low incidence of bulk storage or refueling fuel temperatures above 95 F. Aircraft wing tank fuel temperatures, in static ground soak and in flight, follow closely the changes in local ambient or free stream total temperature. Fuselage or body tank fuel temperatures in static ground soak or in flight, have a gradual change with respect to large differences in local ambient or free stream temperature. The sources and levels of heat loads from aircraft and engine are established. Fuel temperatures are significantly influenced by the power requirements, the environment, and the design for thermal integration of the engine and aircraft fuel systems. The results of the MINEX thermal stability tests show a wide range in relative quality level for the fuels tested. The overall results indicate that aircraft and engine systems can be designed to operate in the Mach 3 range using present primary type fuels and state-of-the-art fluid system components.